Understanding knowledge management strategies in institutions of higher learning and the corporate world: A systematic review - Nasir Koranteng Asiedu; Mercy Abah; De-Graft Johnson Dei (Cogent Business & Management, 2022)
Knowledge management is a popular concept among many disciplines in higher learning institutions. Notwithstanding, reviewed literature shows that, the concept is highly practiced by corporate entities as compared to institutions of higher learning. A systematic review was done to specifically examine the various knowledge management strategies that are used by higher learning institutions considering the popularity of the concept coupled with the fact that it is taught widely across institutions of higher learning. The review was done with over 40 publications of varied topics on knowledge management. These were retrieved from various academic search engines and databases. The study found that, there is inadequate literature on knowledge management strategies in higher learning institutions; however, codification and personalization were generally identified in most of the studies as the main strategies of knowledge management. Strategies like, communities of practice, knowledge partnering and knowledge harvesting were suggested by this study. Higher learning institutions are therefore encouraged to start practicing what they teach by conducting more empirical studies on the concept.
Keywords: 650; communities of practice; corporate world; higher learning institutions; Knowledge management; knowledge management strategies; knowledge partnering; systematic review